2020
DOI: 10.1055/s-0040-1708557
|View full text |Cite
|
Sign up to set email alerts
|

Early Neuromuscular Blockade in Children with Pediatric Acute Respiratory Distress Syndrome

Abstract: Pediatric acute respiratory distress syndrome (PARDS) is a challenging problem with high mortality. Role of neuromuscular blockade in the management of ARDS to date has been controversial, and this study was done to study the role of neuromuscular blockade in children having PARDS and development of associated complications, if any. This was a prospective, case–control study conducted in the pediatric intensive care unit (PICU) of a tertiary care teaching hospital, over a period of 24 months. Patients of age 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
2
Order By: Relevance
“…In particular, NMBA+ patients had a 60% increased risk of in-hospital mortality. Our findings are different from some smaller studies that did not demonstrate an increased mortality in patients who received NMBAs (4, 9, 20). However, previous studies were limited to narrow populations, such as PARDS patients, who may benefit significantly more from an NMBA infusion, as suggested by previous reports (20, 21).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, NMBA+ patients had a 60% increased risk of in-hospital mortality. Our findings are different from some smaller studies that did not demonstrate an increased mortality in patients who received NMBAs (4, 9, 20). However, previous studies were limited to narrow populations, such as PARDS patients, who may benefit significantly more from an NMBA infusion, as suggested by previous reports (20, 21).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are different from some smaller studies that did not demonstrate an increased mortality in patients who received NMBAs (4, 9, 20). However, previous studies were limited to narrow populations, such as PARDS patients, who may benefit significantly more from an NMBA infusion, as suggested by previous reports (20, 21). Our study included children with a wide variety of diseases, including patients undergoing congenital heart surgery or bone marrow transplants, at the more severe end of the illness spectrum admitted to PICU.…”
Section: Discussioncontrasting
confidence: 99%
“…Literature characterizing outcomes of survivors of PARDS has grown substantially since PALICC 2015 (4). We now have information about recovery after PICU admission for PARDS in single-center, multicenter, and population-based studies (14, 17–20, 23–36, 39). Unfortunately, it is increasingly clear that morbidity after hospital discharge from PARDS is common and affects all domains of function, HRQL, and patients’ families.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, patients evaluated 3-4 years following PARDS requiring extracorporeal membrane oxygenation (ECMO) had ongoing impairments as demonstrated by mean POPC score of 2.3 and mean PCPC score of 1.9 (27). In a study specifically evaluating neuromuscular outcomes following neuromuscular blockade for treatment of PARDS, neither myopathy nor neuropathy was identified at 3-month follow-up (39).…”
Section: Justificationmentioning
confidence: 99%
“…Our group found that continuous administration of NMBAs significantly improved oxygenation in patients with moderate-tosevere PARDS [12]. The Paediatric Acute Lung Injury Consensus Conference (PALICC) and the Paediatric European Mechanical Ventilation Consensus Conference (PEMVECC) recommended that clinical trials investigating the short-and long-term outcomes of NMBA use are much needed, especially as-despite the lack of evidence-NMBAs are often used in the most critically ill paediatric patients [13][14][15][16][17][18]. Furthermore, the possible beneficial effects of NMBAs must be outweighed against side-effects such as critical illness polyneuropathy and myopathy (CIPNM), a phenomenon that has been observed especially in adults who are on concurrent corticosteroids or have renal failure [19].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%